2021
DOI: 10.25259/jcis_2_2021
|View full text |Cite
|
Sign up to set email alerts
|

Radiology Performed Fluoroscopy-Guided Lumbar Punctures Decrease Volume of Diagnostic Study Interpretation – Impact on Resident Training and Potential Solutions

Abstract: Objectives: Lumbar punctures performed in radiology departments have significantly increased over the last few decades and are typically performed in academic centers by radiology trainees using fluoroscopy guidance. Performing fluoroscopy-guided lumbar punctures (FGLPs) can often constitute a large portion of a trainee’s workday and the impact of performing FGLPs on the trainee’s clinical productivity (i.e. dictating reports on neuroradiology cross-sectional imaging) has not been studied. The purpose of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Furthermore, FGLPs can be disruptive to both trainees in academic practices and radiologists. 7,8 Performing FGLPs on outpatients without a bedside attempt also appears to be common practice, with only 10.6% of respondent indicating that they always require a bedside attempt before performing an FGLP on outpatients. FGLPs have a high success rate, and we suspect that FGLPs are requested by outpatient clinicians to potentially decrease the inconvenience of a longer procedure and possibly requiring a return for a second attempt if the bedside LP is unsuccessful.…”
Section: Bedside Lp Attempt Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, FGLPs can be disruptive to both trainees in academic practices and radiologists. 7,8 Performing FGLPs on outpatients without a bedside attempt also appears to be common practice, with only 10.6% of respondent indicating that they always require a bedside attempt before performing an FGLP on outpatients. FGLPs have a high success rate, and we suspect that FGLPs are requested by outpatient clinicians to potentially decrease the inconvenience of a longer procedure and possibly requiring a return for a second attempt if the bedside LP is unsuccessful.…”
Section: Bedside Lp Attempt Requirementsmentioning
confidence: 99%
“…While radiology trainees need to learn to perform FGLPs as part of their clinical training and they provide no added cost to the radiology department for performing this service, it is important to not overburden trainees with performing a superfluous number of FGLPs to avoid impacting their diagnostic neuroradiology training. Richards et al 8 reported that for each FGLP performed by a radiology resident, there was a predictable and significant decrease in the number of diagnostic cross-sectional neuroradiology studies that they read in a day. Increased use of physician extenders in academic centers may help relieve some of the burden on trainees of performing increasing number of FGLPs.…”
Section: Use Of Trainees and Physician Extenders To Perform Fglpsmentioning
confidence: 99%